SOCIOPRAGMATIC ANALYSIS OF HATE SPEECH IN HILARION HEAGY’S CONVERSION NEWS ON TWITTER - M. Ferizqo Fahdiyansyah; Susiati, Susiati (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This research discusses the phenomenon of hate speech in Hilarion Heagy's conversion news on Twitter. Hilarion Heagy, a former Orthodox priest who later embraced Eastern Catholicism before ultimately converting to Islam, has sparked significant controversy within religious circles, eliciting varied reactions, especially on social media. This research addresses a significant gap in the literature by examining hate speech in the context of religious conversion. Therefore, this research aims to identify types of hate speech and find out the intent behind hate speech. This research utilizes the National Police Chief's circular number SE/6/X/2015 to identify types of hate expressions and uses Searle's illocutionary speech act theory to explain the meaning behind hate expressions. In this research, data was taken from comments on Twitter related to the news of Hilarion Heagy's conversion. The results of the research found that the expressions of hatred in the news about Hilarion Heagy's conversion were related to religious issues. The outcomes found five types of hate speech, with the most performed being Blasphemy (17 times), followed by Provoking (11 times), Defamation (10 times), Insult (7 times), then the least one being Spreading fake news (5 times). As for the types of illocutionary acts, the most dominant was Assertive (40 times), followed by Directive (7 times) and Expressive (3 times). There were no Commissive and Declaration types found at all.